Middle class imaginaries of Cairo's waste: The zabaleen's story retold - Zaki, Manar (AUC Knowledge Fountain, 2018)
Cairo's informal garbage collectors known as the zabaleen, have been the subject of a plethora of research. Their communities in Cairo have been acknowledged for producing a high rate of garbage recycling. Nevertheless, the relation of the zabaleen with their surrounding spaces has endured much friction. The cumbersome job of collecting and carrying the trash is situated within the spheres of neoliberal policies adopted by the government, the supporting organizations that have praised and endorsed their existence, and most importantly, the middle class households that have been the source of garbage for the zabaleen. Ironically, the zabaleen's job and presence have been met with much support as well as criticism. The zabaleen's reaction to the neoliberal policies has been illustrated in research and the media as a steadfast stance which has helped them survive several challenges and continue with their daily work of collecting the enormous amount of garbage generated in Cairo. The present study attempts to delineate the zabaleen's existence in Cairo from the viewpoints of the entities that are in contact with the garbage collectors: the government, the nongovernmental organizations and the middle classes of Cairo. The research situates the zabaleen within the neoliberal spatial and temporal trajectory of the urban and through the lens of the middle class.